C AND C++ PROGRAMMING LANGUAGES CAPABILITIES AND DIFFERENCES - Abrorjon Kholmatov; Abdurahimova Mubiyna (Galaxy International Interdisciplinary Research Journal, 2023)
Both languages are renowned for their efficiency and versatility, making them popular choices for various applications, from system programming to application development